HUBUNGAN PENGETAHUAN IBU DENGAN KEJADIAN PNEUMONIA PADA BALITA DI PUSKESMAS KEBUN HANDIL KOTA JAMBI - Salvita Fitrianti (Jurnal Akademika Baiturrahim Jambi, 2018)
Pneumonia is one of the biggest health problems and the leading cause of death of children under five years old (infants). The public health center Kebun Handil is the public health center with the highest number of pneumonia infants in Jambi city as many as 222 toddlers in 2016.           This study aimed at determining the correlation of mother’s knowledge and the characteristics of the house with the incidence of pneumonia in infants at the public health center Kebun Handil Jambi city. This is a quantitative research, using Cross Sectional design, and the population of this research is all of infants at the public health center Kebun Handil year 2016 as many as 3.731. The sample was using Accidental Sampling technique, as many as 94 people. This research used Chi Square test. The research was conducted at the public health center Kebun Handil.    The findings indicated that almost respondents (56.4%) have low knowledge, and (53.2%) infants respondents with pneumonia. The result of analysis bivariateChi-Square indicated that there is the correlation between mother’s knowledge with pneumonia in infants (p-value = 0.003 < alpha 0.05). It is necessary to increase the extension to the public about pneumonia toddlers in order to improve the knowledge of the respondents. The counseling results are expected to increase public knowledge of pneumonia and its prevention.